Performance characteristic of digital peak current mode control switching power supply - Furukawa, Yudai; Maeda, Shusuke; Kurokawa, Fujio; Colak, Ilhami (EPE '15 ECCE-Europe : 2015 17th European Conference on Power Electronics and Applications : 8-10 September 2015, 2015)
The purpose of this paper is to discuss performance characteristic of digital peak current mode control switching power supply. The proposed method can capture the peak current value in real time by using the voltage controlled oscillator (VCO), the programmable delay circuit and the signal frequency detector. Its transfer function is derived analytically. Also, the frequency characteristics are revealed using the loop transfer function in the case of different voltage control loop gains. In addition, its gain margin and phase margin are discussed. Furthermore, the transient responses of proposed method are compared with the conventional voltage mode control in the simulation and the experiment.